Green economy studies amongst the global climate change challenge between 2016 and 2022: a bibliometric review - Zhu, Jinsheng Jason; Zhang, Ruitian; Kanhalikham, Kesone; Liu, Zitao; Shen, Xiaoping (Frontiers in Ecology and Evolution, 2023)
Practical and theoretical advancements have not caught pace with rising scientific researches in the rapidly emerging economy undertaking a shift to a more sustainable economy, particularly green economy. After the UN adopted the 2030 Agenda for Sustainable Development, there has been a surge in interest in the green economy among academics around the world, and the literature on the issue is proliferating. This paper adopts the methodology of systematic review and thematic analysis to summarize the relevant literature on areas related to the theme of green economy. The literature was obtained from the Web of Science database and the literature was analyzed using VOSviewer as well as the R language to couple the literature by keywords, country, affiliation, author, publication. The findings of the current paper show that the green economy has received more academic attention from scholars after 2016. The green economy is relatively leading in Asia and Europe. In the context of climate change, future research is anticipated to concentrate on establishing a green economy for global economic growth. This paper makes a substantial contribution to future research on the green economy.